College Automation System - Mishra, Swati; Naskar, Utpal; Dutta, Arkanil; Sahu, Sanchita; Chatterjee, Sourajit; Mazumdar, Sumana (International Journal of Computer Sciences and Engineering, 2025)
College Automation System Project will work on college area network. It will include all the four departments in the college. It will have admission system for, class attendance, online notes and notice board , placement systems so that their students can get all the information by using their valid registration id and password. Let us see how this College Automation System Project will work. College Automation System Project will also help the college administrator. Administrator will able to get all the information regarding any faculty members on particular day and time. Admin panel will also able to edit the login display panel of teachers, staff members, students etc.Admin can add person, delete person, can give special permission. Admin can schedule classes, their lectures time. Teachers can get information of any students under their particular class. Teachers can also make query by using grade, percentage, can see list of students who comes under the category of attendance shortage and many more under this one roof.For student section, they can get any particular teacher’s notes of particular day and other information regarding their campus, such as placement session details, upcoming companies in particular month, their criteria, their venue details and many more. Student section will also include learning section, so that students can prepare for their exams.